The incidence, characteristics, management and outcomes of anaphylaxis in pregnancy: a population‐based descriptive study. (3rd January 2018) - McCall, SJ; Bunch, KJ; Brocklehurst, P; D'Arcy, R; Hinshaw, K; Kurinczuk, JJ; Lucas, DN; Stenson, B; Tuffnell, DJ; Knight, M
Abstract : Objective: The aim of this study was to estimate the incidence of anaphylaxis in pregnancy and describe the management and outcomes in the UK. Design: A population‐based descriptive study using the UK Obstetric Surveillance System (UKOSS). Setting: All consultant‐led maternity units in the UK. Population: All pregnant women who had anaphylaxis between 1 October 2012 and 30 September 2015. Anaphylaxis was defined as a severe, life‐threatening generalised or systemic hypersensitivity reaction. Methods: Prospective case notification using UKOSS. Main outcome measures: Maternal mortality, severe maternal morbidity, neonatal mortality and severe neonatal morbidity. Results: There were 37 confirmed cases of anaphylaxis in pregnancy, giving an estimated incidence of 1.6 (95% CI: 1.1–2.2) per 100 000 maternities. Four cases of anaphylaxis were in women with known penicillin allergies: two received co‐amoxiclav and two cephalosporins. Twelve women had anaphylaxis following prophylactic use of antibiotics at the time of a caesarean delivery. Prophylactic use of antibiotics for Group B streptococcal infection accounted for anaphylaxis in one woman. Two women died (5%), 14 (38%) women were admitted to intensive care and seven women (19%) had one or more additional severe maternal morbidities, which included three haemorrhagic events, two cardiac arrests, one thrombotic event and one pneumonia. No infants died; however, in those infants whose mother had anaphylaxis before delivery ( n  = 18) there were seven (41%) neonatal intensive care unit admissions, three preterm births and one baby was cooled for neonatal encephalopathy. Conclusions: Anaphylaxis is a rare severe complication of pregnancy and frequently the result of a reaction to antibiotic administration. This study highlights the seriousness of the outcomes of this condition for the mother. The low incidence is reassuring given the large proportion of the pregnant population that receive prophylactic antibiotics during delivery. Tweetable abstract: Anaphylaxis is a rare severe complication of pregnancy and frequently the result of a reaction to antibiotic administration. Tweetable abstract: Anaphylaxis is a rare severe complication of pregnancy and frequently the result of a reaction to antibiotic administration.